Application of Cutaneous Stimulus Slow Stroke Back Massage to Reducing Pain Intensity in Patients with Rheumatoid Arthritis - Grace Tedy Tulak; Ekawati Saputri; Risqi Wahyu Susanti; Bestfy Anitasari (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Rheumatoid Arthritis is a disease of the musculoskeletal system characterized by inflammation of the lining of the synovial joints. The most common symptoms are pain and deformity. One of the non-pharmacological pain management that can be done is Slow Strike Back Massage (SSBM). This study aims to apply Slow Stroke Back Massage (SSBM) to reduce pain intensity in patients with Rheumatoid Arthritis. This study used a pre-experimental method with a pretest-posttest design, observations were made with a total sample of 16 people. Sampling was done by accidental sampling technique. The results of data analysis using the Wilcoxon test obtained a value of p = 0.000 which means that there is an effect of SSBM on reducing pain intensity in patients with Rheumatoid Arthritis. From the results of this study it is hoped that the SSBM technique can be applied as a non-pharmacological therapy to reduce pain in patients with Rheumatoid Arthritis.